Peran Program Belajar Sore Mahasiswa KKN Universitas Nusa Nipa terhadap Peningkatan Motivasi dan Kualitas Belajar Anak Desa Mbengu - Yoseph Darius Purnama Rangga; Agustina Fausta; Maria Yunita Heret; Angelina Bare Tapun; Maria Melania; Enjelina Hestia Du’a Ana; Sonia Satriawaty Baragau; Anastasia Nona Riasna (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
The afternoon tutoring program organized by the students of the Community Service Program (KKN) from Nusa Nipa University in Mbengu Village represents a community engagement effort aimed at improving the quality of primary education in rural areas. The background of this activity lies in the low learning motivation and the limited basic literacy and numeracy skills (reading, writing, and arithmetic) still experienced by many elementary school students, both in lower and upper grades. This condition poses a challenge to the teaching and learning process, thereby requiring innovation and structured academic assistance. The main objective of this program is not only to strengthen students’ academic skills but also to foster motivation, independence, and self-confidence in learning. The implementation method consisted of three stages: preparation, execution, and evaluation. The program was conducted at the Holy Cross Parish of Mauloo on July 6, 12, 23, and 28, 2025, with a frequency of once per week. During the activities, KKN students divided participants into small groups based on their level of ability. Each group received assistance in reading, writing, arithmetic, completing school assignments, and engaging with supplementary materials. These were delivered through interactive approaches such as discussions, question-and-answer sessions, and educational games designed to make learning enjoyable and meaningful. The results demonstrated significant improvements in students’ learning motivation, attendance discipline, active participation, and willingness to ask questions. Overall, the program proved effective in enhancing both the motivation and the quality of learning among elementary school students. Moreover, this activity can serve as a relevant alternative learning strategy that may be applied in rural areas through collaboration between university students, local communities, and schools.